Dual energy x-ray absorptiometry and quantitative ultrasound are not interchangeable in diagnosing abnormal bones. Issue 9 (1st May 2012) - Williams, J E; Wilson, C M; Biassoni, L; Suri, R; Fewtrell, M S
Abstract : Objective: To evaluate whether dual energy x-ray absorptiometry (DXA) and quantitative ultrasound (QUS) classify the same children as 'abnormal' (SD (z) score (SDS) ≤−2). Methods: Speed of sound (SOS) was measured at the radius and tibia using QUS and lumbar spine bone mineral density (BMD) using DXA in 621 subjects aged 5–20 years; healthy 412, cystic fibrosis 117 and obese 92. Results: BMD SDS positively (p<0.001) and tibia SOS SDS negatively correlated with size (p<0.05). Disagreement between DXA and QUS for 'abnormal' scans occurred in 6–31%. Those with abnormal BMD and normal SOS SDS had lower mean BMI SDS than those with normal BMD and abnormal SOS SDS. SOS measurements were unobtainable in some children, especially in the obese group. Conclusions: DXA and QUS identify different individuals as 'abnormal'. Agreement between BMD and tibia SOS is lower in obese subjects. Without a gold-standard, it is difficult to determine which technique is more 'correct'.